Social memory among the literati of Yehud - Ben Zvi, Ehud 1951-; Walter de Gruyter GmbH & Co. KG (Berlin Boston De Gruyter, 2019)
Ehud Ben Zvi has been at the forefront of exploring how the study of social memory contributes to our understanding of the intellectual worldof the literati of the early Second Temple period and their textual repertoire. Many of his studies on the matter and several new relevant works are here collected together providing a very useful resource for furthering research and teaching in this area.The essays included here address, inter alia, prophets as sites of memory, kings as sites memory, Jerusalem as a site of memory, a mnemonic system shaped by two interacting 'national' histories, matters of identity and othering as framed and explored via memories, mnemonic metanarratives making sense of the past and serving various didactic purposes and their problems, memories of past and futures events shared by the literati, issues of gender constructions and memory, memories understood by the group as 'counterfactual' and their importance, and, in multiple ways, how and why shared memories served as a (safe) playground for exploring multiple, central ideological issues within the group and of generative grammars governing systemic preferences and dis-preferences for particular memories
Frontmatter -- Foreword -- Table of Contents -- Introduction -- On Social Memory and Identity Formation in Late Persian Yehud: A Historian's Viewpoint with a Focus on Prophetic Literature, Chronicles and the Deuteronomistic Historical Collection -- Remembering the Prophets through the Reading and Rereading of a Collection of Prophetic Books in Yehud: Methodological Considerations and Explorations -- Prophetic Memories in the Deuteronomistic Historical and the Prophetic Collections of Books -- The Yehudite Collection of Prophetic Books and Imperial Contexts: Some Observations -- The Memory of Abraham in Late Persian/Early Hellenistic Yehud/Judah -- Exploring the Memory of Moses 'The Prophet' in Late Persian/Early Hellenistic Yehud/Judah -- Squaring Circles and The Social Benefits of Squaring Them: Joshua as a Case Study for Constraints, Preferences, Balances and Flexibility within the Complex Memory System of the Literati of the late Persian/early Hellenistic Period -- Isaiah, a Memorable Prophet: Why was Isaiah so Memorable in the Late Persian/Early Hellenistic Periods? Some Observations -- Remembering Hosea: The Prophet Hosea as a Site of Memory in Persian Period Yehud -- Reading the Book of Hosea, Remembering Hosea and Thinking of Exile in Yehud -- Readers, Social Memory, Deuteronomistic Language and Jeremiah: The Roles of Deuteronomistic Language in Shaping Memories of Jeremiah among Late Persian/early Hellenistic Readers of the Book of Jeremiah -- Chronicles and Samuel-Kings: Two Interacting Aspects of one Memory System in the Late Persian/Early Hellenistic Period -- Shaping and Remembering an Arch-Villain in the Late Persian/Early Hellenistic Period: The Case of Ahaz in Chronicles and its Implications -- Reshaping the Memory of Zedekiah and His Period in Chronicles -- Reading Chronicles and Reshaping the Memory of Manasseh -- Toward a Sense of Balance: Remembering the Catastrophe of Monarchic Judah/(Ideological) Israel and Exile through Reading Chronicles in Late Yehud -- Chronicles and Its Reshaping of Memories of Monarchic Period Prophets: Some Observations -- Contributions of the Genealogies in Chronicles to the Shaping of the Memory of the Monarchic Period: The Case of Some Simeonites's Vignettes -- A Balancing Act: Settling and Unsettling Issues Concerning Past Divine Promises in Historiographical Texts Shaping Social Memory in the Late Persian Period -- A Contribution to the Intellectual History of Yehud: The Story of Micaiah and Its Function within the Discourse of Persian-Period Literati -- When Yhwh Tests People: General Considerations and Particular Observations Regarding the Books of Chronicles and Job -- Exploring Jerusalem as a Site of Memory in the Late Persian and Early Hellenistic Periods -- Remembering Pre-Israelite Jerusalem in Late Persian Yehud: Mnemonic Preferences, Memories and Social Imagination -- Re-Negotiating a Putative Utopia and the Stories of the Rejection of Foreign Wives in Ezra-Nehemiah -- The "Successful, Wise, Worthy Wife" of Proverbs 31:10-31 as a Source for Reconstructing Aspects of Thought and Economy in the Late Persian/Early Hellenistic Period -- Monogynistic and Monogamous Tendencies, Memories and Imagination in Late Persian/Early Hellenistic Yehud -- Othering, Selfing, 'Boundarying' and 'Cross-Boundarying' as Interwoven with Socially Shared Memories: Some Observations -- Total Exile, Empty Land and the General Intellectual Discourse in Yehud -- The Voice and Role of a Counterfactual Memory in the Construction of Exile and Return: Considering Jeremiah 40:7-12 -- Potential Intersections Between Research Frames Informed by Social-Memory and 'Bourdieusian' Approaches/Concepts: The Study of Socio-Historical Features of the Literati of the early Second Temple Period -- Social Sciences Models and Mnemonic/Imagined Worlds: Exploring Their Interrelations in Ancient Israel -- Bibliography -- Index of Authors -- Index of References to Ancient Sources
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Collective Memory -- Yehud (Persian province); Rabbinical literature -- Yehud (Persian province) -- History and criticism; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Collective Memory -- Yehud (Persian province); RELIGION / Biblical Criticism & Interpretation / Old Testament; Ancient Israel; Early Second Temple; Hebrew Bible; Social Memory; Aufsatzsammlung